Acute Stress Response Profiles in Health Workers Facing SARS-CoV-2 - Moderato, Luca; Lazzeroni, Davide; Oppo, Annalisa; Dell’Orco, Francesco; Moderato, Paolo; Presti, Giovambattista (Frontiers in Psychology, 2021)
Objective: The study is an explorative investigation aimed to assess the differences in acute stress response patterns of health workers facing Covid-19 during Italy first lockdown. Methods: A cross-sectional investigation using convenience sampling method was conducted in Italy during April 2020. Eight hundred and fifty-eight health workers participated in the research filling out self-report measures including Patient Health Questionnaire (PHQ-9), Generalized Anxiety Disorder (GAD-7), Insomnia Severity Index (ISI), and Impact of Event Scale–Revised (IES-R). Results: Moderate/severe depression was found in 28.9% (95%CI: 25.8-32.04), moderate/severe anxiety in 55.4% (95%CI: 51.9-58.8), insomnia in 15% (95%CI: 12.5-17.5), and distress in 52.5% (95%CI: 48.5%-56.6) of participants. The 3% of health workers reported frequent suicidal thoughts. Female sex, working for >15 hours/week in a Covid-19 unit, and living apart from family were associated with a significantly higher risk of distress, anxiety, insomnia, depression, and functional impairment. Four profiles were identified on the basis of psychopathological measures: Profile_0 included 44% (N = 270), Profile_1 25.6% (N = 157), Profile_2 19.1% (N = 117) , and Profile_3 11.3% (N = 69) of participants. Results showed a significant effect for Profiles X IES-R (η2 = 0.079; f = 0.29) indicating that in all profiles, except for Profile_0, avoidance scale is lower than hyperarousal and intrusion symptoms scales of the IES-R. This characteristic could be a probable index of the control exerted by the responders to not fly away from their job. Conclusion: The identification of specific profiles could help psychiatrists, and emergency psychologists to build specific interventions in terms of both primary and secondary prevention to face future waves of the Covid-19 outbreak.